2021
DOI: 10.3390/ijerph182413328
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Prevalence among Physicians: A Systematic Review and Meta-Analysis

Abstract: Background: Smoking is a major public health problem. Although physicians have a key role in the fight against smoking, some of them are still smoking. Thus, we aimed to conduct a systematic review and meta-analysis on the prevalence of smoking among physicians. Methods: PubMed, Cochrane, and Embase databases were searched. The prevalence of smoking among physicians was estimated and stratified, where possible, by specialties, continents, and periods of time. Then, meta-regressions were performed regarding put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 248 publications
2
18
0
Order By: Relevance
“…In addition, smoking behavior showed significant gender differences. Male physicians had a much higher smoking rate than female physicians (34.15 vs. 1.59%), which is consistent with the vast majority of studies ( 8 ). To improve this, we can start by changing the stereotype that smoking is an act of masculinity, thus reducing the prevalence of smoking in the male emergency physician population and even in the general male population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, smoking behavior showed significant gender differences. Male physicians had a much higher smoking rate than female physicians (34.15 vs. 1.59%), which is consistent with the vast majority of studies ( 8 ). To improve this, we can start by changing the stereotype that smoking is an act of masculinity, thus reducing the prevalence of smoking in the male emergency physician population and even in the general male population.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have been conducted worldwide on the current status of smoking among physicians. The results of a meta-analysis that included 246 papers showed that smoking rates varied widely among physicians practicing different specialties ( 8 ). The smoking rate was 9% for radiologists, 18% for surgeons, 22% for internists, and 24% for family physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other studies, the prevalence of current smoking in Swiss physicians is similar to the prevalence reported in Israel (8%) ( Wilf Miron et al, 2019 ), exceeds figures documented in the United States and Northern Ireland (4%) ( Frank et al, 1998 , McGrady et al, 2007 , Frank, 2000 Oct ) and is inferior to the prevalence found in Poland (15%) ( Znyk et al, 2019 ) or in France (18% ( Desprès et al, 2010 ) or 32% ( Josseran et al, 2005 ). It is a much lower smoking rate than the one found in a recent meta-analysis, showing 24% smoking among family practitioners ( Besson et al, 2021 ). The results we observed in our study were in concordance with previous research, showing a decrease in the prevalence of smoking tobacco over the years in both physicians and in the general population ( Frank et al, 1998 , Sebo et al, 2007 , McGrady et al, 2007 , Juel et al, 1999 , Frank, 2000 Oct , Desprès et al, 2010 , Besson et al, 2021 , Põld and Pärna, 2017 , Garfinkel and Stellman, 1986 ).…”
Section: Comparison To Existing Literaturementioning
confidence: 76%
“…It is a much lower smoking rate than the one found in a recent meta-analysis, showing 24% smoking among family practitioners ( Besson et al, 2021 ). The results we observed in our study were in concordance with previous research, showing a decrease in the prevalence of smoking tobacco over the years in both physicians and in the general population ( Frank et al, 1998 , Sebo et al, 2007 , McGrady et al, 2007 , Juel et al, 1999 , Frank, 2000 Oct , Desprès et al, 2010 , Besson et al, 2021 , Põld and Pärna, 2017 , Garfinkel and Stellman, 1986 ).…”
Section: Comparison To Existing Literaturementioning
confidence: 76%
“…In addition, the stress and workload among medical students are especially high [ 46 ], and education surrounding nutrition also seems to be inadequate [ 25 ]. Worldwide, the prevalence of smoking among medical students is 25% [ 47 ] even though awareness of the risks that tobacco has on their health should be higher. Night shifts and a heavy workload play a major role in explaining the unhealthy lifestyle among health professionals [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%